Histomorphological Study on the Testes of Non-descript Male Goats (Capra hircus) - Ankit Damor; Balwant Meshram; Hemant Joshi; Mahendra Kumar Saini; Sandeep Kumar; Sanjay Chouhan; Pawan Kumar; Poonam Saini (Indian Journal of Veterinary Anatomy, 2026)
The buck’s testicles were suspended in the scrotum by the spermatic cords and positioned vertically, just in front of the inguinal area. Each testes had two surfaces, two borders, and two ends. The lateral surface was convex, while the medial surface was flat.The testis’s caudomedial border was joined to the epididymis.Testes consisted of several important structures, including the tunica albuginea, trabeculae, mediastinum testis, seminiferous tubules, and interstitial tissue.The testes were covered by the visceral layer of the tunica vaginalis and tunica albuginea, which is mainly composed of collagen fibres.The outermost layer was the tunica albuginea, which consisted of a strong layer of connective tissue and smooth muscle fibres. The basement membrane supported the seminiferous tubules.Separate rows of spermatogenic cells were positioned from the seminiferous tubule’s basement membrane towards the lumen. They were Spermatogonia, Primary spermatocytes, Secondary spermatocytes, Spermatids and Spermatozoa.